THE IMPORTANCE OF INFORMATION COMUNICATION TECNOLOGY ( ICT ) IN EDUCATIONAL ATTAINMENT AMONG STUDENTS OF THE HIGHER INSTITUTE OF SCIENCE AND TECHNOLOGY (H.I.S.T) -AZIZIA (Comprehensive Journal of Science, 2026)
The ICT and its related technologies play a ubiquitous part in modern life due to the unlimited availability of data , services and uses. One of the technologies that has changed the world is the internet , This study investigates an important subject of the importance of ICT especially the  Internet usage among students of the Higher Institute of Science and Technology (H.I.S.T) –AZIZIA in educational purposes. In particular, the study identifies the extent of their Internet use in study, and the obstacles and barriers that limit their use. The study uses descriptive survey method and designed questionnaire carried out among 80 students as a study sample. With statistical significance, the results revealed that there was a low percentage of Internet use for studying purposes by students in the Institution. Moreover, students believe that the internet can save time to prepare scientific research. In addition,  no web site belongs to the institution, and the lack of computers containing software, and poor internet services were the most obstacles facing the suitable utilization of the Internet by (H.I.S.T)to accomplish educational attainment. Furthermore, the results revealed that there is no correlation between academic attainment and number of hours of Internet use.